Evolving Surgical Approaches to Bicuspid Aortic Valve Associated Aortopathy - Fatehi Hassanabad, Ali; Feindel, Christopher M.; Verma, Subodh; Fedak, Paul W. M. (Frontiers in Cardiovascular Medicine, 2019)
Bicuspid aortic valve (BAV) is the most common congenital cardiac pathology which results from the fusion of two adjacent aortic valve cusps. It is associated with dilatation of the aorta, known as bicuspid valve-associated aortopathy or bicuspid aortopathy. Bicuspid aortopathy is progressive and is linked with adverse clinical events. Hence, frequent monitoring and early intervention with prophylactic surgical resection of the proximal aorta is often recommended. Over the past two decades resection strategies and surgical interventions have mainly been directed by surgeon and institution preferences. These practices have ranged from conservative to aggressive approaches based on aortic size and growth criteria. This strategy, however, may not best reflect the risks of important aortic events. A new set of guidelines was proposed for the treatment of bicuspid aortopathy. Herein, we will highlight the most recent findings pertinent to bicuspid aortopathy and its management in the context of a case presentation.